An adaptive cache switching based video streaming using Buffer seeded multi checkpoint peer responder to improve the quality of service in WSN - et. al., S.Priyadharisini, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
The widespread of online video access by the various user become huge in recent days by direct streaming through the internet. However, video streaming in wireless networks consumes more delay due to response from the service provider. Due to high bandwidth consideration, the quality of streaming video consumes more buffer state to load the data. By this mitigation, the loss quality becomes problematic to access the service continually. To resolve this problem, we propose an On-Demand Service-Based Peer Switching (ODSBPS) for video streaming using Buffer seeded multi checkpoint peer responded to improve the quality of service in WSN. Initially, these methods verify the service request load based on the energy consumption in multi-channel service responder. Based on the Energy-Aware Traffic Flow Estimation (EATFE) verifies the buffer state from the nearest peer to create a checkpoint. This nearest checkpoint is estimated based on Streaming Service Intense Access Rate (SSIAR). Through this SSIAR checkpoint, the data is loaded on reserved cache points to create buffer points. Simultaneously the nearest peer responder checks the previous checkpoint to load the seed into the peer end. The peer end verifies the last buffer checkpoint to stream continuous service to make low energy level streaming provide the best video streaming service.